Gain Improvement of Dual Band Antenna Based on Complementary Rectangular Split-Ring Resonator. (20th March 2012) - Ortiz, Noelia; Falcone, Francisco; Sorolla, Mario
Abstract : A simple and successful dual band patch linear polarized rectangular antenna design is presented. The dual band antenna is designed etching a complementary rectangular split-ring resonator in the patch of a conventional rectangular patch antenna. Furthermore, a parametric study shows the influence of the location of the CSRR particle on the radiation characteristics of the dual band antenna. Going further, a miniaturization of the conventional rectangular patch antenna and an enhancement of the complementary split-ring resonator resonance gain versus the location of the CSRR on the patch are achieved. The dual band antenna design has been made feasible due to the quasistatic resonance property of the complementary split-ring resonators. The simulated results are compared with measured data and good agreement is reported.